2022
DOI: 10.3390/nano12030479
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of Graphene Oxide Doxorubicin Loading Capacity Based on Density Functional Theory

Abstract: Graphene can be used as a drug carrier of doxorubicin (DOX) to reduce the side effects of doxorubicin. However, there is limited research on the surface chemical modifications and biological effects of graphene oxide (GO). Therefore, it is necessary to explore the DOX affinity of different oxygen-containing functional groups in the graphene system. We constructed graphene system models and studied the structure and distribution of epoxy and hydroxyl groups on the carbon surface. Based on molecular dynamics sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
(39 reference statements)
1
7
1
Order By: Relevance
“…The results suggest that increased oxygen density on the surface affects the binding affinity of the drug, and optimization of functional groups renders controllability over drug loading, which can lead to a better drug delivery system. 57 The poly-dispersity index is an important parameter in determining the properties of polymers. Even though many studies are available on graphene and GO conjugated with PEG polymers, Mina Mahdavi et al have investigated the loading of DOX on GO surface conjugated with PEG chains (PEGGO) of different lengths and their effect on the adsorption pattern of the drug on the surface of the carrier (Fig.…”
Section: Carbon-based Materials For Drug Deliverymentioning
confidence: 99%
“…The results suggest that increased oxygen density on the surface affects the binding affinity of the drug, and optimization of functional groups renders controllability over drug loading, which can lead to a better drug delivery system. 57 The poly-dispersity index is an important parameter in determining the properties of polymers. Even though many studies are available on graphene and GO conjugated with PEG polymers, Mina Mahdavi et al have investigated the loading of DOX on GO surface conjugated with PEG chains (PEGGO) of different lengths and their effect on the adsorption pattern of the drug on the surface of the carrier (Fig.…”
Section: Carbon-based Materials For Drug Deliverymentioning
confidence: 99%
“…Moreover, putting aside the weak DOX interaction in the sp 3 region, GO has a nanostructure that has the potential to reduce DOX cytotoxicity caused by drug resistance and poor internalization [200]. This year, a study emerged revealing that the previously stated weakness of DOX absorption can be controlled by adding a hydroxyl group to GO [201]. The more hydroxyl groups, the stronger the electron affinity for DOX, further increasing the DOX loading capacity of GO.…”
Section: Graphenementioning
confidence: 99%
“…The yellow and blue areas represent an increase and decrease in charge density, respectively. Adapted from [ 63 ], copyright 2022, MDPI.…”
Section: Figurementioning
confidence: 99%
“…When DOX was adsorbed onto GO, 0.05 electrons were transferred from DOX to GO-O and the GO-OH-O surface, respectively. Additionally, 0.07 electrons are transferred from DOX to the GO-OH surface [ 63 ], see Figure 3 . Thus, using density functional theory calculations, it was confirmed that different O -moieties had different affinities for DOX.…”
Section: Introductionmentioning
confidence: 99%